Stress Level Among Customer Service Executives In Business Process Outsourcing Industry (BPO) In Malaysia - Factors Contributing To Stress - Ramasami, Suthithra (2007)
The purpose of this study will be to collect an access data that will reflect factors(variables) that contributes to stress level among Information System (IS) employees in BPO industry. The focus of this study will be to provide findings to improve further on the areas that cause stress. The findings will help the growth of BPO industry in Malaysia by tackling work related stress appropriately.